Pemanfaatan Membran Nitroselulosa untuk Pengiriman Antigen Uji dalam Deteksi TMV dengan DIBA - Susamto Somowiyarjo; Y. B. Sumardiyono; Suharno Suharno (Jurnal Perlindungan Tanaman Indonesia, 1997)
Simplification of dot immunobinding assay (DIBA) by using TMV-infected samples which were stored and mailed in nitrocellulose membrane (NCM) was described. The antigenicity of TMV in DIBA could be maintained in leaf extract-dotted NCM which had been stored at 29ºC al least for 42 days. The method was developed for sending samples using infected leaf extract-dotted NCM to replace fresh samples. By this method, the antigenicity of the virus could he detected after they have been sent to 18 places which took time from 7 to 26 days. It ts anticipated that the simplicity of DIBA using mailed samples will lead to DIBA's rapid adoption for development of central diagnosis facilities to support the viral diseases management. It may also have wider use in DIBA-based screening and survey programs for plant viruses and could overcome plant quarantine restriction.